LECTURER JOB SATISFACTION AFFECTED BY DISCIPLINE AND MOTIVATION MEDIATED BY ORGANIZATIONAL COMMITMENT - Duha, Timotius (Jurnal Aplikasi Manajemen, 2018)
The research aims to examine and analyze the influence of discipline, motivation, and organizational commitment towards job satisfaction of lecturers in STKIP South Nias. Data was collected by distributing questionnaires to 64 lecturers of STKIP South Nias. A sampling technique used was probability sampling with simple random sampling method;data test technique was used in this research including validity, reliability test with. WhereasPathAnalysis was used to verify and to prove the research hypothesis. Analysis result demonstrated that discipline had a positive influence towardsorganizational commitment,motivation had a positive influence towardsorganizational commitment, the organizational commitment had a positive influence towards job satisfaction,as well as discipline and motivation, had a positive influence towards job satisfaction through organizational commitment.